Persepsi siswa terhadap pembelajaran daring mata pelajaran pendidikan jasmani olahraga dan kesehatan - Helmi Yuhdana Haryanto; Saifullah Arif (YLPK Mahardhika, 2021)
In this study, the background is the difference in perceptions of SMK Negeri 10 Semarang students in learning the subjects of Physical Education, Sports and Health (PJOK). So that it can be seen that the purpose of this study is to determine the perceptions of students, with the hope that it can be used as a reference in providing learning methods in the next academic year. The number of samples used was 112 students using the simple random sampling technique. This study concluded that the perceptions of SMK Negeri 10 Semarang students had a positive perception of learning PJOK subjects that could be categorized as good with an average percentage of 83.7%. This can be used as a reference in providing future learning techniques to use the same method so that students can understand the material well and are motivated to follow PJOK subjects. Students do not experience boredom in the process of teaching and learning activities.